Electrical properties of mim structures based on vanadium-borate glass; Soviet Physics Journal; Vol. 24, № 3 - Kalygina V. M.; Kosintsev V. I. Victor Ivanovich; Gaman V. I.; Modebadze O. E.; Nikolaev A. I. (1981, 1981)
The results are given of investigation of the dc and ac electrical properties of thin-film metal-insulator-metal structures of capacitor type based on glass of the composition 35% B2O3-15% CaO-20% V2O4-30% V2O5 (wt.%). The glass films were deposited by an explosive method on a glassceramic substrate at t°=80°C. Upper and lower Nichrome electrodes were obtained by thermal evaporation. The influence of annealing on the conductivity and current-voltage characteristics of such structures was investigated. It was found that the current-voltage characteristics before and after annealing are determined in a wide range of temperatures and constant electric fields by contact barriers on the metal-glass-film interface. The ac behavior of the samples at f >102 Hz is due to the bulk properties of the glass film